Effect of thermal maturation on chemical structure and nanomechanical properties of solid bitumen. (April 2018) - Liu, Yuke; Xiong, Yongqiang; Li, Yun; Peng, Ping'an
Abstract: An abundance of organic matter is present as solid bitumen in highly mature shales. Changes in chemical structure of solid bitumen during catagenesis could alter the way its mechanical properties evolve. This study considers a series of solid bitumen samples artificially produced from the pyrolysis at 420–618 °C of soluble organic matter which originated from Maoming shale, to examine alternations in their chemical structure, nano-morphological and mechanical properties during maturation. Solid-state 13 C nuclear magnetic resonance spectroscopy and elemental analysis were employed to characterize the structural changes. Young's modulus and microstructures were determined by atomic force microscopy. The results show that both structural (including C/H atomic ratio and carbon aromaticity) and mechanical (Young's modulus) variations in solid bitumen exhibit two staged evolutions (i.e., wet gas stage and dry gas stage) during maturation. In the wet gas stage (EasyRo 1.85%–2.64%), the C/H ratio and carbon aromaticity increase substantially with maturation, and the solid bitumen is relatively compliant with an average Young's modulus varying from 2.7 ± 0.6 to 3.0 ± 0.6 GPa. When maturity reaches to dry gas stage (EasyRo 2.64%–4.59%), structural parameters do not change greatly, whereas solid bitumen becomes much stiffer with modulus rising sharply to 7.2 ± 1.1 GPa at EasyRo 3.49% and further gently to 8.8 ± 1.4 GPa at EasyRo 4.59%. Concomitantly, great variations are observed on surface morphology, and the degree of heterogeneity in solid bitumen is recorded to be increasingly high along thermal simulation. Given the strong correlation between structural parameters and Young's modulus, we suggest that the stiffening of solid bitumen is extensively affected by its structural condensation due to the loss of aliphatic carbons and the increase of aromaticity. Highlights: A series of solid bitumen samples were artificially produced from the pyrolysis (420–618 °C) of soluble organic matter. Chemical structure of solid bitumen was characterized by solid-state 13 C nuclear magnetic resonance spectroscopy. Nanomechanical property of solid bitumen was determined by atomic force microscopy. Changes of both chemical structure and mechanical properties show two staged evolutions. The stiffening of solid bitumen with increasing maturation is affected by its structural condensation.